Deciphering the Role of Various Signaling Pathways in the Pathophysiology of Depression - Vashisht, Etash; Vats, Vishal; Verma, Ravinder; Parashar, Jatin; Garg, Vandana; Dutt, Rohit; Mittal, Vineet; Singh, Govind; Kaushik, Deepak (Current Signal Transduction Therapy, 2023)
Background: Depression is one of the leading causes of disability around the globe. In the early years of depression, it is hypothesized that neurotransmitters have a major or dominant role in depression pathophysiology. The roles of different parts of the brain and neurotransmitters have emerged at different intervals of time, and various hypotheses beyond monoamines have arisen. In this review, numerous theories that have been proposed in the last 60 years are covered based on the literature.Methodology: This review was prepared with literature and data presented from different databases including PubMed, Frontier in Pharmacology, Elsevier, Journal of Depression and Anxiety, etc.Results: The different hypotheses of depression have been presented in different eras. Each hypothesis of depression tries to explore different aspects of depression, which shifts the pathogenesis of depression approaches towards bio-molecule and genetic roles.Conclusion: The pathophysiology of depression is very complex. None of the hypotheses alone can explain the pathophysiology of depression. All of these hypotheses are interconnected with each other. Through these hypotheses, it can be concluded that neuro-inflammation can be the base of depression and by reducing this factor we can overcome this problem.
Keywords: BH4 pathway